Price Dynamics in North Maluku 2025: Seeking a Balance Between Stability and People's Welfare - Nurul Hidayah (PT Bukuloka Literasi Bangsa, 2025)
This study analyzes the dynamics of inflation and deflation in North Maluku Province throughout 2025, exploring its implications for sustainable investment interest and community welfare levels. Using secondary data from the North Maluku Central Statistics Agency (BPS) and other relevant sources, this study identifies patterns of monthly and annual price fluctuations, as well as the potential risks and opportunities they pose. The results of the analysis show that moderate annual inflation creates the preconditions for stability desired by investors, but frequent episodes of monthly deflation, especially in local commodities, have the potential to suppress the productivity and income of the agro-maritime sector and delay investment decisions. In terms of welfare, moderate inflation provides room for increased purchasing power, but deflation can erode the income of local producer groups and increase the real debt burden. Policy recommendations focus on specific instruments such as the Micro Logistics Cluster Regional Regulation, the Agro-Maritime Downstreaming Blueprint, and the Productivity Services Voucher Scheme to transform price stability into economic productivity and sustainable welfare improvement in North Maluku. Keywords: Inflation, Deflation, Sustainable Investment, Community Welfare, North Maluku, RPJMD.